Geistliches Erzählen: zur deutschsprachigen religiösen Kleinepik des Mittelalters - Eichenberger, Nicole (Hermaea, 2015)
Despite the richness of its facets, the short religious epic has been largely neglected by scholars until now. This study explores this literary phenomenon using a multi-perspectival descriptive model. Extensive detailed case studies provide basic information and present the genre in its broader literary historical and systematic context. --